Respuesta :

The equation is set equal to 0 and the parenthesis are joined together by multiplication.
So, set each one of the mini-expressions inside the parenthesis to 0.
We do this because anything multiplied by 0 equals 0.

2m+3=0
2m=-3
m=-3/2

4m+3=0
4m=-3
m=-3/4

So, the answers are -3/2 and -3/4.

Hope his helps!
I'm assuming you're looking for the distributed form of the equation :)

An easy acronym for multiplying binomials is FOIL, short for First, Out(er/side), In(ner/side), and Last.

First;
Multiply the first two numbers of the binomials:
(2m + 3)(4m + 3) = 0
2m * 4m = 8m²

Out;
Multiply the two outer monomials:
(2m + 3)(4m + 3) = 0
2m * 3 = 6m

In;
Multiply the two inner monomials:
(2m + 3)(4m + 3) = 0
3 * 4m = 12m

Last;
Multiply the last two monomials:
(2m + 3)(4m + 3) = 0
3 * 3 = 9

Add all the answers up, set equal to 0, then simplify:
[tex] 8m^{2}+6m+12m+9=0\\8m^{2}+18m+9\\\\ Thus,\ your\ answer\ is:\\ 8m^{2}+18m+9=0[/tex]


As an after-note, I realised I should probably also show how to solve for the values of m ,:D

Starting with the original binomials, set each equal to 0 and solve for m:

[tex] (2m+3)(4m+3)=0\\\\2m+3=0\\2m=-3\\m=\frac{-3}{2}\\\\4m+3=0\\4m=-3\\m=\frac{-3}{4}[/tex]

Thus, m = -3/2 and m = -3/4.
ACCESS MORE